A 28 nm CMOS 10 bit 100 MS/s Asynchronous SAR ADC with Low-Power Switching Procedure and Timing-Protection Scheme - Fang Tang (116243) (2021)
This paper presents a 10 bit 100 MS/s asynchronous successive approximation register (SAR) analog-to-digital converter (ADC) without calibration for industrial control system (ICS) applications. Several techniques are adopted in the proposed switching procedure to achieve better linearity, power and area efficiency. A single-side-fixed technique is utilized to reduce the number of capacitors; a parallel split capacitor array in combination with a partially thermometer coded technique can minimize the switching energy, improve speed, and decrease differential non-linearity (DNL). In addition, a compact timing-protection scheme is proposed to ensure the stability of the asynchronous SAR ADC. The proposed ADC is fabricated in a 28 nm CMOS process with an active area of 0.026 mm2. At 100 MS/s, the ADC achieves a signal-to-noise-and-distortion ratio (SNDR) of 51.54 dB and a spurious free dynamic range (SFDR) of 55.12 dB with the Nyquist input. The measured DNL and integral non-linearity (INL) without calibration are +0.37/−0.44 and +0.48/−0.63 LSB, respectively. The power consumption is 1.1 mW with a supply voltage of 0.9 V, leading to a figure of merit (FoM) of 35.6 fJ/conversion-step. Other Information Published in: Electronics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/electronics10222856